Influence of Adolescent Reproductive Health Promotion Media Booklet on Knowledge and Attitude of Adolescents Living in Work Area of Ibrahim Adjie Public Health Center in 2018 - Sri Hennyati Amiruddin; Sri Komalaningsih; Ma'mun Sutisna; Hidayat Wijayanegara; Leri Septiani; Herry Garna (Universitas Islam Bandung, 2020)
Adolescent period is a critical period that requires quality health services. The aim of this study was to analyze the effect of health education through booklet media on the knowledge and attitude towards reproductive health among adolescents. This was a quasi-experimental case control study with nonequivalent two group design conducted on 282 students of SMP Negeri 37, a public junior high school, in the work area of Ibrahim Adjie Public Health Center in Bandung city during December 2018–May 2019. Subjects were divided into two groups, intervention and control groups, with 141 subjects in each group. Data collected were tested for normality and homogeneity using Kolmogorov-Smirnov and Levene tests, respectively, followed by a bivariate analysis using Wilcoxon test to determine the difference. Knowledge of all students in both groups was poor during pre-test with an increase found in 135 subjects (95.7%) in the intervention group (p=0.001) and 63 subjects (44.7%) in the control group (p=0.003) based on the post-test results. Negative attitude was also seen in both groups during pre-test, with a shift towards positive attitude was evident in 134 students (95.0%) in the intervention group (p=0.001) and 117 students (83.0%) in the control group (p=0.002) based on post-test results. This presence that health information conveyed through booklet has a probability of giving 0.995 times stronger influence leaflet. Thus, the use of booklet can improve knowledge and attitude towards adolescent reproductive health. PENGARUH BOOKLET MEDIA PROMOSI KESEHATAN REPRODUKSI REMAJA TERHADAP PENGETAHUAN DAN SIKAP REMAJA YANG BERTEMPAT TINGGAL DI WILAYAH KERJA PUSKESMAS IBRAHIM ADJIE TAHUN 2018Masa remaja merupakan masa kritis yang membutuhkan pelayanan kesehatan yang berkualitas. Tujuan penelitian ini adalah menganalisis pengaruh pendidikan kesehatan melalui media booklet terhadap pengetahuan dan sikap remaja tentang kesehatan reproduksi. Penelitian ini merupakan penelitian quasi-experimental case control dengan rancangan nonequivalent two group yang dilaksanakan terhadap 282 siswa/i SMP Negeri 37 di wilayah kerja Puskesmas Ibrahim Adjie Kota Bandung selama Desember 2018–Mei 2019. Subjek dibagi menjadi dua kelompok, yaitu kelompok intervensi dan kontrol dengan 141 subjek di setiap kelompok. Data yang terkumpul diuji normalitas dan homogenitasnya masing-masing menggunakan Uji Kolmogorov-Smirnov dan Levene, dilanjutkan dengan analisis bivariat menggunakan Uji Wilcoxon untuk mengetahui perbedaannya. Pengetahuan semua siswa pada kedua kelompok kurang saat pre-test dengan peningkatan pengetahuan 135 subjek (95,7%) pada kelompok intervensi (p=0,001) dan 63 subjek (44,7%) pada kelompok kontrol (p=0,003) berdasar atas hasil post-test. Sikap negatif juga terlihat pada kedua kelompok selama pre-test dengan pergeseran ke arah sikap positif 134 siswa (95,0%) pada kelompok intervensi (p=0,001) dan 117 siswa (83,0%) pada kelompok kontrol (p=0,002) berdasar atas hasil post-test. Informasi kesehatan yang disampaikan melalui media booklet ini berpeluang memberikan pengaruh 0,995 kali lebih kuat daripada media leaflet. Dengan demikian, penggunaan booklet dapat meningkatkan pengetahuan dan sikap remaja terhadap kesehatan reproduksi. Simpulan, terdapat pengaruh pendidikan kesehatan melalui media booklet terhadap pengetahuan dan sikap remaja tentang kesehatan reproduksi.